2020
DOI: 10.1021/jacs.0c03459
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Metallo-Supramolecules under Kinetic or Thermodynamic Control: Characterization of Positional Isomers Using Scanning Tunneling Spectroscopy

Abstract: Coordination-driven self-assembly has been extensively employed to construct a variety of discrete structures as a bottom-up strategy. However, mechanistic understanding regarding whether self-assembly is under kinetic or thermodynamic control is less explored. To date, such mechanistic investigation has been limited to distinct, assembled structures. It still remains a formidable challenge to study the kinetic and thermodynamic behavior of self-assembly systems with multiple assembled isomers due to the lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…These coordination bonds originate from the 5d orbital electrons of the gold atom. On-surface coordination has been studied with various d-block metals, including Au, Co, Cu, and Fe, and ligands containing such functional groups as cyano, isocyano, pyridyl, or carboxy that form coordination bonds that differ from those produced in solution chemistry. , For example, a threefold coordination to d-block metal is typically encountered on surfaces ,, but not in solution. There have been several attempts to elucidate the oxidation states of metal–organic complexes formed by on-surface chemical reactions, but the charge states and energy levels of the central metal and ligands with respect to the coordination number still remain unclear in these cases.…”
mentioning
confidence: 99%
“…These coordination bonds originate from the 5d orbital electrons of the gold atom. On-surface coordination has been studied with various d-block metals, including Au, Co, Cu, and Fe, and ligands containing such functional groups as cyano, isocyano, pyridyl, or carboxy that form coordination bonds that differ from those produced in solution chemistry. , For example, a threefold coordination to d-block metal is typically encountered on surfaces ,, but not in solution. There have been several attempts to elucidate the oxidation states of metal–organic complexes formed by on-surface chemical reactions, but the charge states and energy levels of the central metal and ligands with respect to the coordination number still remain unclear in these cases.…”
mentioning
confidence: 99%
“…a dichloromethane solution of L (Table 1). The crystal structure of [ZnL 3 ] n (BF 4 ) 2n was built as a pcu net (point symbol 4 12 6 3 ) showing 3-fold interpenetrated frameworks (Fig. 1a).…”
Section: Crystal Structuresmentioning
confidence: 99%
“…A self-assembly process between metal cations and electrondonor ligands allows for construction of coordination compounds and introduction of functions at the molecular level. [1][2][3] Network structures by control of building blocks and relatively large voids usually have been reported as resulting in metal-organic frameworks (MOFs) and coordination polymers (CPs) boasting the structural advantages such as high thermal stability, molecular rigidity, and specic hydrophilicity of voids. 4 Many research groups have reported useful coordination compounds for gas adsorption, 5 chiral molecule detection, 6 and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effective characterization techniques are highly demanded for investigating the supramolecules with dissymmetrical ligands. In recent years, scanning tunneling microscopy (STM) has emerged as a powerful tool to characterize supramolecular assemblies, since it can directly image each individual structure at submolecular resolution and reflect the population of each isomer in the complex system …”
Section: Introductionmentioning
confidence: 99%